Pattern Recognition of MRI Findings in Patients with Non-Ketotic Hyperosmolar Hyperglycemic State- A Clinico-Radio-Biochemical Parameter Study - M. Dinesh; Anila Punchiry; Harshavardhan Balaganesan; Ram Gopal Karumuri (Asian Journal of Medical Radiological Research, 2020)
Background: Hyperosmolar hyperglycemic state is a complication of diabetes mellitus in which high blood sugar results in high osmolarity without significant ketoacidosis. The present study assessed MRI findings in patients with hyperosmolar hyperglycemic state. Subjects and Methods: 58 patients reported with hyperosmolar hyperglycemic state of both genders underwent MRI. Results: Out of 58 patients, males were 30 and females were 28. We found that clinical presentation were focal motor seizures in 25, multiple myoclonic jerks in 20, generalized tonic clonic seizures in 10 and complex partial seizures in 3 cases. The difference was non- significant (P> 0.05). The mean blood glucose level found to be 482.4 mg/dl, HbA1C was 12.1%, Na+/K+ level was 134.2/4.6 mmol/l and serum osmolarity was 305.8 mOsm/Kg. Conclusion: Clinical presentation were focal motor seizures, multiple myoclonic jerks, generalized tonic clonic seizures and complex partial seizures. T2/FLAIR was hyperintense, DWI showed restriction and SWAN was isointense.